PERSEPSI MAHASISWA CALON GURU TERHADAP PEMANFAATAN SPATIAL.IO SEBAGAI VIRTUAL LEARNING EXPERIENCE BERBASIS METAVERSE - Lutfi Khoerunnisa; Rullyana, Gema; Linda Setiawati; Fikri Dwi Oktaviani; Liddya Ganda Asmara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore pre-service teachers’ perceptions of the use of Spatial.io as a metaverse-based virtual learning experience in higher education. The study is grounded in the growing demand for learning experiences that are more immersive, interactive, and contextual, particularly in response to the limitations of conventional online learning in fostering engagement and social presence. A descriptive quantitative approach with a survey design was employed. Data were collected through an online questionnaire using a five-point Likert scale developed based on the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, encompassing five dimensions: performance expectancy, effort expectancy, social influence, facilitating conditions, and behavioral intention. The respondents consisted of 300 active students enrolled in teacher education programs in Indonesia, selected through convenience sampling. The findings indicate that all UTAUT dimensions fell within the high category, with the highest mean found in facilitating conditions (4.04), followed by social influence (4.02), performance expectancy (4.00), behavioral intention (3.98), and effort expectancy (3.90). These findings suggest that pre-service teachers demonstrate a positive acceptance of Spatial.io, particularly due to the availability of supporting facilities and the influence of the academic environment. However, the ease-of-use dimension still requires further attention. This study highlights the potential of Spatial.io to be developed as an innovative pedagogical space in teacher education, provided that its integration is supported by technical training, well-structured instructional design, and sustained institutional support.